Barbie : a day at the fair - Pugliano, Carol; S.I. International (Firm) (New York : Random House, 2003)
Barbie and Kelly go to the fair and even ride the ferris wheel.
Keywords: Fairs -- Fiction; Ferris wheels -- Fiction; Dolls -- Fiction